MR Imaging and Clinical Characteristics of Diffuse Glioneuronal Tumor with Oligodendroglioma-like Features and Nuclear Clusters - Benesch, M.; Perwein, T.; Apfaltrer, G.; Langer, T.; Neumann, A.; Brecht, I.B.; Schuhmann, M.U.; Cario, H.; Frühwald, M.C.; Vollert, K.; van Buiren, M.; Deng, M.Y.; et al. (American Journal of Neuroradiology, 2022)
BACKGROUND AND PURPOSE: Diffuse glioneuronal tumor with oligodendroglioma-like features and nuclear clusters (DGONC) is a new, molecularly defined glioneuronal CNS tumor type. The objective of the present study was to describe MR imaging and clinical characteristics of patients with DGONC.MATERIALS AND METHODS: Preoperative MR images of 9 patients with DGONC (median age at diagnosis, 9.9 years; range, 4.2–21.8 years) were reviewed.RESULTS: All tumors were located superficially in the frontal/temporal lobes and sharply delineated, displaying little mass effect. Near the circle of Willis, the tumors encompassed the arteries. All except one demonstrated characteristics of low-to-intermediate aggressiveness with high-to-intermediate T2WI and ADC signals and bone remodeling. Most tumors (n = 7) showed a homogeneous ground-glass aspect on T2-weighted and FLAIR images. On the basis of the original histopathologic diagnosis, 6 patients received postsurgical chemo-/radiotherapy, 2 were irradiated after surgery, and 1 patient underwent tumor resection only. At a median follow-up of 61 months (range, 10–154 months), 6 patients were alive in a first complete remission and 2 with stable disease 10 and 21 months after diagnosis. The only patient with progressive disease was lost to follow-up. Five-year overall and event-free survival was 100% and 86±13%, respectively.CONCLUSIONS: This case series presents radiomorphologic characteristics highly predictive of DGONC that contrast with the typical aspects of the original histopathologic diagnoses. This presentation underlines the definition of DGONC as a separate entity, from a clinical perspective. Complete resection may be favorable for long-term disease control in patients with DGONC. The efficacy of nonsurgical treatment modalities should be evaluated in larger series.DNETdysembryoplastic neuroepithelial tumorHITBrain Tumor NetworkDGONCdiffuse glioneuronal tumor with oligodendroglioma-like features and nuclear clustersPNETprimitive neuroectodermal tumor